PREVALENCE OF CHRONIC KIDNEY DISEASE – PRELIMINARY RESULTS EH-UH 2 STUDY (CROATIAN SCIENTIFIC FOUNDATION). (June 2022) - Domislovic, Marija; Gellineo, Lana; Jelakovic, Ana; Fucek, Mirjana; Begic, Zvonimir; Frkanec, Stjepan; Katic, Luka; Radunovic, Danilo; Prelevic, Vladimir; Stevanovic, Ranko; Dika, Zivka; Karanovic, Sandra; et al.
Abstract : Objective: According to the results of epidemiological studies, the worldwide prevalence of chronic kidney disease (CKD) is 9.1% with an observed trend of increasing over the last thirty years. High prevalence is a consequence of worldwide epidemics of arterial hypertension, diabetes, obesity but also aging of the population. The data on the prevalence of CKD in Croatia are scarce. Our aim was to determine the prevalence of CKD in Croatia and to determine the stages of CKD according to the KDIGO guidelines. Design and method: Data on 781 subjects (Croatian general adult population) which were enrolled in a nationwide survey (EH-UH 2) from 2018–2020 (mean age 59 yr., 34.7% male) were analysed. CKD EPI equation was used to estimate glomerular filtration rate (eGFR) in total group. CKD was defined according to the guidelines as a value of eGFR < 60 mL/min/1.73 m 2 . Subjects were distributed depending on the eGFR value in stages of CKD. Results: Prevalence of CKD in Croatia is 10.1%, with higher prevalence among women (10.4% vs. 9.6%, p = 0.820). Prevalence of CKD according to the CKD stages is 9.3% for G3a and G3b, 0.6% for G4 and 0.1% for G5. When looking at age characteristics, there is a sharp increase in the prevalence of CKD in the eighth decade (Figure 1). The prevalence of diabetes is 14%, obesity 39%, and arterial hypertension 63% in the whole group. Conclusions: These preliminary results of EH-UH 2 study show that the prevalence of CKD is high in Croatia, with women being affected more than men. Our data are consistent with global prevalence data of CKD.